Arylation reaction of N-dichlorophosphoryl-P-trichlorophosphazene - Arslan, M; Aslan, F; Ozturk, AI (John Wiley & Sons Inc, 2003)
The reactions of N-dichlorophosphoryl-P-trichlorophosphazene (Cl3P=N-POCl2) with phenylmagnesium chloride, o-tolylmagnesium chloride, p-tolylmagnesium chloride, p-chlorophenylmagnesium chloride, 2-mesitylmagnesium bromide, and 2-thienyl lithium were studied. The resulting pentaaryl phosphazenes R3P=N-P(O)R-2 were separated by using column chromatography, their structures were defined by IR, elemental analysis, H-1, C-13, P-31 NMR, and mass spectroscopy. (C) 2003 Wiley Periodicals, Inc.
Keywords: Phosphorus-Nitrogen Compounds; Chain Linear Phosphazenes; Block-Copolymers; Crystal-Structure; Side Groups; Aminolysis; Polymerization; Chemistry